2010
DOI: 10.2298/sarh1008420s
|View full text |Cite
|
Sign up to set email alerts
|

Oral health status in patients with diabetes mellitus type 2 in relation to metabolic control of the disease

Abstract: The study indicates that there is a relationship between poor control of diabetes and caries, and periodontal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
(16 reference statements)
1
8
2
Order By: Relevance
“…Additionally, diabetic patients often report excessive thirst and polyuria, and the literature supports an association between dental caries and poorly controlled diabetes. 23 However, this association is not always observed, as was the case in the present study. 24 Gastroesophageal reflux (GER) is another common characteristic in this group of patients, and this condition has been investigated as a potential causal agent of dental caries.…”
contrasting
confidence: 60%
“…Additionally, diabetic patients often report excessive thirst and polyuria, and the literature supports an association between dental caries and poorly controlled diabetes. 23 However, this association is not always observed, as was the case in the present study. 24 Gastroesophageal reflux (GER) is another common characteristic in this group of patients, and this condition has been investigated as a potential causal agent of dental caries.…”
contrasting
confidence: 60%
“…Another study denies such correlation 60 . Many cross-sectional clinical studies found higher prevalence of dental caries for subjects with diabetes both type 1 9,61 and type 2 62,63 . Also, positive correlation of caries with duration of diabetes 62 , type of diabetes 62 and metabolic control has been reported 62,63 .…”
Section: Dental Cariesmentioning
confidence: 99%
“…Many cross-sectional clinical studies found higher prevalence of dental caries for subjects with diabetes both type 1 9,61 and type 2 62,63 . Also, positive correlation of caries with duration of diabetes 62 , type of diabetes 62 and metabolic control has been reported 62,63 . On the contrary, a number of authors have not found the correlation between dental caries and diabetes, type of diabetes, duration of disease, metabolic control and the existence of diabetic complications 64 .…”
Section: Dental Cariesmentioning
confidence: 99%
“…3 There is already evidence for the existence of a bidirectional relationship between diabetes and oral health. 2 Subsequently, providing diabetic care without integrating oral healthcare is an access to care issue. Physicians and insurance companies who facilitate concurrent dental care to their diabetic patients will improve their diabetic patients' outcomes.…”
Section: The Argument For Integration In the Hospital Teammentioning
confidence: 99%